2020
DOI: 10.1111/1750-3841.15018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the buffer capacity of ingredients in salad dressing products

Abstract: The pH of most acid food products depends on undefined and complex buffering of ingredients but is critically important for regulatory purposes and food safety. Our objective was to define the buffer capacity (BC) of ingredients in salad dressing products. Ingredients of salad dressings were titrated individually and in combination using concentrations typical of dressing products. Titration curves from pH 2 to 12 were generated with sodium hydroxide and hydrochloric acid, which were then used to generate BC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…4), we found that α = 0.5 resulted in a BC model for pH 2 to 12 that had model results similar to observed BC data. By default, we used 15 sine–cosine paired terms, which were sufficient to approximate most BC curves generated for acid and low‐acid food ingredients (Longtin et al., 2020). The trigonometric regression results for the acetic acid BC data are shown in Figure 4B (black line).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4), we found that α = 0.5 resulted in a BC model for pH 2 to 12 that had model results similar to observed BC data. By default, we used 15 sine–cosine paired terms, which were sufficient to approximate most BC curves generated for acid and low‐acid food ingredients (Longtin et al., 2020). The trigonometric regression results for the acetic acid BC data are shown in Figure 4B (black line).…”
Section: Resultsmentioning
confidence: 99%
“…We include data on pH prediction with sodium and calcium (monovalent and divalent cations) chloride, under a variety of pH conditions, to be relevant to food matrices, including recently developed calcium‐based vegetable fermentations (MccFeeters & Perez‐Diaz, 2010). A companion paper (Longtin, Price, Mishra, & Breidt, 2020) reports data from BC models for a variety of acid and low‐acid ingredients in salad‐dressing products. Once the BC of an acid or low‐acid ingredient is known, the magnitude of pH changes due to the addition of that ingredient to acid or acidified foods may be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, buffer models have been used to characterize how acid and low‐acid salad dressing ingredients influence product pH (Longtin et al., 2020). Buffer models have also been used to link pH with fermentation acid concentrations during vegetable fermentations, and to help quantify the pH impact of the malolactic reaction of lactic acid bacteria (Breidt & Skinner, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Food ingredient buffering can be estimated by using a titration method to generate buffer capacity (BC) curves over a pH range of 2–12 (Longtin et al., 2020) where there is little or no buffering from water. Outside of this pH range, buffering is essentially the same for aqueous food products, due to the symmetrical increase in buffering of water at the low and high extremes of the pH scale (Butler & Cogley, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation